Effect of pulsed electric field (PEF) on mass transfer andquality parameters of osmodehydrated fruits – a review - Tylewicz, Urszula (Engineering Sciences And Technologies, 2017)
Recently the development of intermediate moisture food products has received huge attention due to the consumer demand for minimally processed products. The removal of moisture is a very important unit operation in food processing, since it enables to stabilize food products and improve their quality retention during storage. Osmotic dehydration (OD) is a useful technology to partially remove water from food material such as fruit and vegetables prior to other stabilising techniques e.g. drying or freezing, at the same time a counter-current solute inflow into the tissue takes place. Unfortunately the cellular membrane exerts high resistances to transfers, therefore the OD is a very long process. There are many pre-treatments that can be used in order to accelerate the mass transfers. Pulsed electric field (PEF) has been recently considered as an alternative pre-treatment method allowing non-thermal damage the cell membranes prior to OD. PEF treatment leads to the electroporation of the cell membrane by applying an external electric field, in the form of short pulses, to the cellular tissue placed between two electrodes. Electroporation of the cell membranes could promote reversible or irreversible pore formation and cell disintegration, depending on both the intensity of the electric field strength applied and the characteristics of the raw materials. The formation of the pores facilitates the water removal from the tissue. Moreover, since PEF is a non-thermal technology it allows to maintain a high quality level in terms of colour and the nutritional value of the final product
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2017, Nr 4 (27), s. 66-78
Keywords: fruit quality; PEF; osmotic dehydration; mass transfer; jakość owoców; odwadnianie osmotyczne; wymiana masy